The Influence of Top Management Team Human Capital on Sustainable Business Growth - Shen, Yaoping; Zheng, Qian; Lei, Xinghui; Hu, Fengpei (Frontiers in Psychology, 2021)
Traditionally, enterprises have subscribed to the belief that top management team (TMT) human capital is of great influence to a specific entity. While long being a question of interest in the field of management, the extant literature rarely discusses the impact of TMT human capital on sustainable business growth. By examining data obtained from 535 TMT members of private enterprises in Zhejiang Province PRC, and investigate the mediating effect of decision-making quality as well as the moderating effect of founder characteristics, we analyze the positive operating mechanisms of TMT human capital on sustainable business growth. Interestingly, the single most striking observation to emerge from the empirical investigation was :(1) TMT human capital has a significant positive impact on sustainable business growth; (2) decision-making quality fully mediates the relationship between TMT human capital and sustainable business growth; and (3) the more open-minded the founders, the stronger the mediating effect of decision-making quality in the relationship between TMT human capital and sustainable business growth. This research has expanded the perspective and scope of the research on TMT human capital, and its practical usage is discussed.